Monte Carlo simulation of delayed γ-rays ionizing the atmosphere based on debris motion model - LIU Li; NIU Shengli; ZUO Yinghong; ZHU Jinhui; ZHUO Jun; LI Xiazhi (He jishu)
BackgroundIn the aftermath of a high-altitude nuclear explosion, the delayed γ-rays emanating from the debris undergo a complex ionization process while traversing the non-uniform high-altitude atmosphere. This process results in a significant augmentation of the electron number density in the ionosphere, thereby affecting radio communication links traversing the ionosphere.PurposeThis study aims to develop a comprehensive modeling and simulation framework that accurately captures the temporal and spatial evolution of delayed γ-ray sources and their corresponding atmospheric ionization effects.MethodsFirstly, a hydrodynamic model was established to simulate the debris motion resulting from a high-altitude nuclear explosion. Subsequently, a hierarchical equivalent model of delayed γ-ray sources was formulated based on the debris parameters. Then, the Monte Carlo method was utilized to simulate the ionization effect of these delayed γ-rays in the non-uniform high-altitude atmosphere. Finally, given the dynamic evolution of the debris shape, a stratified sampling approach was employed to determine the initial positions of the delayed γ-rays. Various conditions such as 4 Mt equivalent explosion at a height of 40 km, 4 Mt equivalent at a height of 80 km, 100 kt equivalent at a height of 40 km, and 100 kt equivalent at a height of 80 km, the fragment cloud was evenly divided into 10 layers according to their respective proportions. MCATNP code was used to calculate the distribution of electron production rates formed by the ionization of the atmosphere by delayed γ-rays generated by the debris different times after the explosion. Furthermore, considering the exponential decay of atmospheric density with height, the mass thickness sampling method was adopted to simplify the computational model.Results & ConclusionsThe results indicate that the ionization intensity and range of delayed γ-rays are significantly influenced by the debris shape. In the case of a megaton-level high-altitude nuclear explosion, the ionization range of delayed γ-rays can extend to over a thousand kilometers. Specifically, with a constant explosion height, an increase in the equivalent yield leads to an augmentation in the debris height and horizontal radius, thereby enhancing the ionization range and intensity. Conversely, when the burst height is increased while maintaining a constant equivalent yield, the debris height and horizontal radius increase, leading to an expansion in the ionization range but a reduction in ionization intensity.